72th Annual Meeting of the APS Division of Fluid Dynamics - Gallery of Fluid Motion 2019
DOI: 10.1103/aps.dfd.2019.gfm.v0055
|View full text |Cite
|
Sign up to set email alerts
|

Video: Life and fate of a bubble in a constricted Hele-Shaw channel

Abstract: Motivated by the desire to understand complex transient behaviour in fluid flows, we study the dynamics of an air bubble driven by the steady motion of a suspending viscous fluid within a Hele-Shaw channel with a centred depth perturbation. Using both experiments and numerical simulations of a depth-averaged model, we investigate the evolution of an initially centred bubble of prescribed volume as a function of flow rate and initial shape. The experiments exhibit a rich variety of organised transient dynamics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(53 citation statements)
references
References 37 publications
(57 reference statements)
4
49
0
Order By: Relevance
“…As a model 'playground' to test these ideas we consider the steady state structure and transient dynamics of two finite air bubbles propagating in a Hele-Shaw channel with a prescribed depth perturbation when the surrounding fluid is extracted at a constant flow rate (see figure 1). In a previous work [9], we showed that a single bubble may break up into two (or more) bubbles depending on its initial spatial configuration and on the flow rate and that, post breakup, the bubbles may either merge back into a single or compound bubble or separate indefinitely (see figure 2). A key result of this study was that the post breakup dynamics were strongly influenced by the existence of weakly unstable steady states that are specific to the two-bubble system.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a model 'playground' to test these ideas we consider the steady state structure and transient dynamics of two finite air bubbles propagating in a Hele-Shaw channel with a prescribed depth perturbation when the surrounding fluid is extracted at a constant flow rate (see figure 1). In a previous work [9], we showed that a single bubble may break up into two (or more) bubbles depending on its initial spatial configuration and on the flow rate and that, post breakup, the bubbles may either merge back into a single or compound bubble or separate indefinitely (see figure 2). A key result of this study was that the post breakup dynamics were strongly influenced by the existence of weakly unstable steady states that are specific to the two-bubble system.…”
Section: Introductionmentioning
confidence: 91%
“…Transient behaviour and steady propagation modes have been investigated extensively in the case of a single-bubble using a mixture of analytical and numerical techniques [see, for example 10,17,20,[32][33][34] and experiments [see, for example 18,21,22,31,38,39]. If a depth-perturbation is added to the bottom of the channel as shown in figure 1, the range of existence and stability of steady propagation modes changes dramatically, as mapped out by Franco-Gómez et al [7,8], Gaillard et al [9], Keeler et al [14]. The solution branches interact in a highly nontrivial manner, resulting in a number of different bifurcations and regions of bi-stability in the system; features absent when there is no geometric perturbation in the channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If so, the unstable branch is not just an insignificant consequence of the fold bifurcation but provides unique insight into the system dynamics. The influence and importance of unstable states in fluid dynamics systems has been investigated in many different contexts, including shear flow [11], droplets [17], finite air bubbles [16,26] and a slide-coating flow [8]. Indeed, as shown in figure 2(b), where the phase-plane is sketched for a generic system with an stable ('attractor') and weakly unstable ('saddle-node') state, the unstable state can act as a separator of dynamical outcomes; the stable manifold is a dividing 'line' and the unstable manifold connects to the stable state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent 3D studies for strongly confined drops [12,13] confirm that the films which confine the drops are not uniform in thickness. These thin films affect the drag on the drop [14][15][16][17] and have an important role in systems with surfactants as they dominate the surface area of the drop, and hence, any surface transport processes [18,19].…”
Section: Introductionmentioning
confidence: 99%